2005
DOI: 10.1111/j.1600-0684.2005.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an immortalized oviduct cell line from the cynomolgus monkey (Macaca fascicularis)

Abstract: To establish reproductive biological techniques in mammals, it is important to understand the growth environment of the embryo. Oviduct epithelial cells are in close proximity to the embryo during pre-implantation development. We, therefore, established an immortalized oviduct epithelial cell line from the cynomolgus monkey, evaluated the usefulness of these cells as feeder cells for embryo culture, and investigated the gene expression of several growth factors and cytokines in the cells. The immortalized cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This would potentially reduce the variation in embryo development often noted in monolayer culture systems. The BOEC-CM is able to support embryo development to the blastocyst stage and improve embryo quality (LoperaVasquez et al 2016a) through secreted embryotrophic components such as OVGP1 (Briton-Jones et al 2004), ET-1 (Reinhart et al 2003), IGF (Xia et al 1996), VEGF, EGF, IGF1, TGFβ2 and IL4 (Okada et al 2005) that have been properly identified.…”
Section: Embryo Development Modelsmentioning
confidence: 99%
“…This would potentially reduce the variation in embryo development often noted in monolayer culture systems. The BOEC-CM is able to support embryo development to the blastocyst stage and improve embryo quality (LoperaVasquez et al 2016a) through secreted embryotrophic components such as OVGP1 (Briton-Jones et al 2004), ET-1 (Reinhart et al 2003), IGF (Xia et al 1996), VEGF, EGF, IGF1, TGFβ2 and IL4 (Okada et al 2005) that have been properly identified.…”
Section: Embryo Development Modelsmentioning
confidence: 99%
“…Reprod., v.13, n.3, p.160-167, Jul./Sept. 2016 163 components such as OVGP1 (Briton-Jones et al, 2004), ET-1 (Reinhart et al, 2003), IGF (Xia et al, 1996;Winger et al, 1997), VEGF, EGF, IGF1, TGFβ2, and IL4 (Okada et al, 2005). However, many other secretions still remain unknown.…”
Section: Oviductal Environment and In Vitro Modelsmentioning
confidence: 99%